5g times g
To simplify the expression 6g - g, you first need to combine like terms. Like terms have the same variable raised to the same power. In this case, both terms have the variable g raised to the power of 1. When you subtract g from 6g, you are left with 5g. Therefore, the simplified form of 6g - g is 5g.
The answer is: 5g - 6
You take out the common factor, namely, "g".
In algebra, when you have an expression like 6g-g, you can simplify it by combining like terms. In this case, the "g" terms are like terms because they have the same variable. So, 6g-g simplifies to 5g, meaning you subtract the coefficient of the second term from the coefficient of the first term while keeping the variable the same.
5g times g
5g - g = 4g
5G - 5 = 100 5g = 100+5 5G = 105 G = 105 divided by 5 g = 21
To simplify the expression 6g - g, you first need to combine like terms. Like terms have the same variable raised to the same power. In this case, both terms have the variable g raised to the power of 1. When you subtract g from 6g, you are left with 5g. Therefore, the simplified form of 6g - g is 5g.
5g is bigger because 5g = 5000 mg
the answeres 5g
No!
5g is the larger quantity.
40
Simplifying 5g = 508mg Solving 5g = 508gm Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-508gm' to each side of the equation. 5g + -508gm = 508gm + -508gm Combine like terms: 508gm + -508gm = 0 5g + -508gm = 0 Factor out the Greatest Common Factor (GCF), 'g'. g (5 + -508m) = 0
The answer is: 5g - 6
You take out the common factor, namely, "g".